Prevalence of Helicobacter pylori infection in adult immune thrombocytopenia patients - Suresh Kumar M; Natarajan M; Palanikumaran V; Prakash V; Vasantha Kalyani D (Asian Journal of Medical Sciences, 2023)
Background: Helicobacter pylori is a Gram-negative, microaerophilic bacteria colonizing more than half of the world’s human stomachs. It is the causal agent of active chronic gastritis and the most common cause of peptic ulceration, including gastric and duodenal ulcers. Aims and Objectives: This study aims to the prevalence of H. pylori infection in adult immune thrombocytopenia (ITP) patients. Materials and Methods: An interventional and prospective study was conducted over 6 months with over 50 ITP patients, including those admitted to the general medicine ward and those in regular follow-up in medicine outpatient department. In addition, in all primary ITP patients, a stool antigen test for H. pylori Ag and baseline complete blood count, including platelet count, were done. In addition, all patients’ platelet count was monitored twice weekly for 6 months. Results: Of the 50 patients, 40 are female and 10 are male. The bleeding manifestation was present in 34 patients (68%) and absent in 16 (32%). Among 34 patients, purpura was more frequent (35.3%), followed by gum bleeding 17.6%. Fourteen people tested positive for the H. pylori antigen. Thirty-six patients were found to be H. pylori antigen negative. H. pylori positive frequency was 28%. Patients who receive both steroids and an H. pylori regimen are 9 (18%). Patients who received the H. pylori regimen were only 5 (10%). Patients only receiving steroid doses are 27 (54%). Conclusion: We conclude that 28% of our study patients are infected with H. pylori, and eradicating this organism significantly improves the platelet count. However, a more extended follow-up period is needed to detect the true prevalence of H. pylori infection and the duration of remission.